A Physical Analog to Assess Surgical Face Mask Air Flow Resistance During Tidal Ventilation - Demoulin, Bruno; Duvivier, Claude; Marchal, François; Demoulin-Alexikova, Silvia (Frontiers in Physiology, 2022)
A large variety of disposable face masks have been produced since the onset of the covid-19 pandemic. Decreased resistance to inspiration improves adherence to the use of the mask; the so called breathability is usually estimated by the measurement of air flow across a section of the tissue under a given pressure difference. We hypothesized that the mask pressure – flow relationship studied in conditions that mimic tidal breathing could allow a more comprehensive characterisation of airflow resistance, a major determinant of mask comfort. A physical analogue was made of a plaster cast dummy head connected through a pneumotachograph to a series of bellows inflated /deflated by a respirator. Pressure was measured at the mock airway opening over which the mask was carefully secured. The precision of the measurement equipment was quantified using two estimates of measurement error: repeatability coefficient (RC) and within-mask coefficient of variation (CVwm). The airflow resistance of 10 surgical masks was tested on 4 different days. Resistance means did not differ significantly among 4 repeated measures (0.34 hPa.s.L-1; 0.37 hPa.s.L-1; 0.37 hPa.s.L-1 and 0.37 hPa.s.L-1; p=0.08), the estimated RC was 0.08 hPa.s.L-1 [95%CI: 0.06 – 0.10 hPa.s.L-1] and CVwm was 8.7% [95%CI: 1.5 – 12.2%]. Multiple comparisons suggest the presence of a learning effect by which the operator reduced the error over the course of repetitive resistance measurements. Measurement precision improved considerably when the first set of measures was not taken into account (RC~0.05 hPa.s.L-1[95%CI: 0.03 – 0.06 hPa.s.L-1]; CVwm~4.5% [95%CI: 1.9 – 6.1%]). The testing of the face mask resistance appears simple and highly repeatable in conditions that resemble tidal breathing, once operator training was assured. The procedure adds further to the current standard assessment of breathability and allows estimating the maximal added respiratory load, about 10 - 20% of the respiratory resistance reported in heathy adult subjects.